Anatomical and Functional Predictors of Permanent Pacemaker Implantation After Transcatheter Aortic Valve Implantation - Jung, Susanne; Kondruweit, Markus; Marwan, Mohamed; Achenbach, Stephan (Journal of the American Heart Association, 2025)
High-degree atrioventricular block with the need for permanent pacemaker (PPM) implantation represents a frequent complication after transcatheter aortic valve implantation (TAVI). Extension of indication for TAVI toward subjects with lower surgical risk requires reduction of the likelihood for the need for PPM implantation. The aim of the current analysis was to identify predictors of the need for PPM implantation after TAVI. In a cohort of 1500 consecutive patients without a PPM undergoing transfemoral TAVI, clinical and procedural characteristics as well as parameters derived from cardiac computed tomography, such as membranous septal length and calcium volumes of the aortic valve cusps and the left ventricular outflow tract were assessed. Median calcium volume of the aortic valve was 552 mm (interquartile range [IQR]: 340-811 mm ) in the group of subjects requiring a PPM, which was higher than in the group of subjects not requiring PPM implantation (455 mm [IQR: 245-723 mm ], =0.001). The same was true for calcification of the noncoronary cusp ( =0.027), left coronary cusp ( =0.033), and right coronary cusp ( =0.006). In multivariable analysis, calcium volume of the noncoronary cusp ( =0.039; odds ratio [OR], 1.089 per 100 mm ), preexisting complete right bundle-branch block ( <0.001; OR, 9.402), and implantation of a self-expandable prosthesis ( <0.001; OR, 1.856) were significantly associated with PPM implantation after TAVI. The current analysis offers a detailed examination of predictors for the need for PPM implantation after TAVI. Our results may contribute to improved risk stratification on the need for PPM implantation after TAVI.